CALCULATION OF PRODUCTION PRICE ANALYSIS IN CV PELANGI ADVERTISING - Pammuji Nugroho, Totok Susilo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2018)
This study aims to determine the cost of production at CV Pelangi Advertising company. The company is engaged in the rental of advertising services which offer a point of location for the use of business people. This research uses qualitative method that is by obtaining company data then compare the method used. Company data used are all cost components that have occurred in 2017 then formulated to be able to make an estimate of cost of production in 2018. The method used to compare the calculation of cost production is company method and full costing method. The results shows that there was a difference between company method and full costing method, where the result of full costing method is bigger. This is because the company method there are several methods that have not been entered so that will affect the calculation of cost of production. Thus the company should use the method of full costing in calculating the cost of goods manufactured. Keywords : company method, full costing method, cost of production